HUBUNGAN TATA KELOLA UNIVERSITAS DAN PROFESIONALITAS DOSEN, DENGAN MUTU LAYANAN PENDIDIKAN - Connie Chairunnisa (Faktor Jurnal Ilmiah Kependidikan, 2015)
Abstract:. The study aims is for to know the ralation governance university and professional lecturer with service quality of education. This research was conducted in correlational technique method, with minimun sample from the whole population to be amount of 60 lecturer, teaching in graduate school Uhamka in Jakarta. The data obtained from the spread of questionnaires and learn some documentation. The analysis data to use correlation analysis, and multiple regression and simple regression. The results show (1) there are relationships positive and significantly between governance university with service quality of education; (2) there are relationships positive and significantly between professional lecturer with service quality of education; (3) there are relationships positive and significantly between governance university and professional lecturer in the same joint with service quality of education. The research concludes that, to strengthen the quality of service of education, the governance university and professional lecturer must be to do with correctly and professional more enhanced, and a serious attention.Keywords: Governance University, Professional lecturer, service quality of education.